STRATEGI PENGEMBANGAN USAHA PRODUK TEH CELUP ROSELA (Hibiscus sabdariffa L.) UD. BALI GENDIS, KLUNGKUNG - Isabela, Tamara; Mulyani, Sri; Satriawan, I Ketut (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2018)
This study aims to identify the internal and external factors, analyzing alternative strategy, and recommends priority strategy. This research using matrix IFE, EFE, SWOT, IE and TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution). The results show that the company has 5 strengths, 6 weaknesses, 4 opportunities and 4 threats in this business. The results showed that the value of internal factor evaluation (IFE) was 3,350 and external factor evaluation (EFE) was 3,063. This value indicated a strong position. In the matrix Internal-External (IE) strategy that must be done was to grow and develop a strategy, which consists an intensive strategies (market penetration, market development and product development) and integrative strategies (backward integration, forward integration, and horizontal integration. Based on SWOT analysis there are 7 alternative strategies that can be recommended to develop UD. Bali Gendis. The result of strategy ranking analysis is promoting periodically and socializing the benefits of rosela tea actively to introduce more products to the public. Keywords : industrial development strategy, UD. Bali gendis , rosela tea, SWOT, TOPSIS